Trends analysis in primary agricultural production off Serbia - Drago Cvijanović; Branko Mihailović; Radovan Pejanović (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
Primary agricultural production is a significant factor of the total national economy, primarily due to its share in GDP and total employment. Together with food industry, this sector has over 15% of Serbian GDP. Although the share of the primary agricultural production in realized GDP has constantly decreasing since the beginning of 2000 (owing to bigger growth of GDP in other sectors of Serbian economy), the primary agriculture significantly contribute to other industrial sectors, which directly depend on raw materials from agriculture, then inputs industry for agriculture, as well as accompanying service activities .Initiated changes in the field of agriculture, although under influence of numerous factors, which have an amortization effect on them, have acquired a character of irreversible processes. A reform of agricultural sector can hardly return to a starting position, but there, first of all, can talk about its vacillating tempo and agrarian policy instruments, which often should set up a balance between diametrically opposite goals. In such conditions, Serbian agriculture has extraordinary place and role in the total economic development of the country, especially in the process of adjusting economic mechanisms for realization of specific social goals, on conduction of reforms and transition, and primarily on mitigation of the world economic/financial crisis' impact, which seriously jeopardize a revival and development of economy.
Keywords: 330; primary agriculture; natural resources; crop farming; livestock breeding; agricultural husbandries